2011
DOI: 10.1002/art.33323
|View full text |Cite
|
Sign up to set email alerts
|

Protease‐activated receptor 2, rather than protease‐activated receptor 1, contributes to the aggressive properties of synovial fibroblasts in rheumatoid arthritis

Abstract: Objective. To investigate whether proteaseactivated receptor 1 (PAR-1) and/or PAR-2 promotes the invasiveness/proliferation of synovial fibroblasts (SFs) and to determine the signaling mechanisms of these pathways.Methods. SFs were isolated from the synovial tissue of patients with rheumatoid arthritis (RA), patients with osteoarthritis (OA), and PAR-1-or PAR-2-knockout (KO) mice. Expression of PAR-1 and PAR-2 was detected by immunofluorescence and Western blotting. The invasion and proliferation of SFs were m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 50 publications
2
30
0
Order By: Relevance
“…However, in periodontal tissues, PAR 2 seems to be upregulated during inflammation, where it is believed to be activated by bacterial and host proteinases, whereas PAR 1 is upregulated during periodontal tissue repair. This counterregulation of PARs actions was also demonstrated by Xue et al [72] in rheumatoid arthritis synovial fibroblasts, where PAR 2 activation was associated with an elevated TNF-alpha release and PAR 1 activation prevented the release of proinflammatory cytokines. Interestingly, da Silva et al [47] showed that PAR 1 overexpression after periodontal treatment was inversely correlated to PAR 2 expression in gingival crevicular fluid cells.…”
Section: Discussionsupporting
confidence: 74%
“…However, in periodontal tissues, PAR 2 seems to be upregulated during inflammation, where it is believed to be activated by bacterial and host proteinases, whereas PAR 1 is upregulated during periodontal tissue repair. This counterregulation of PARs actions was also demonstrated by Xue et al [72] in rheumatoid arthritis synovial fibroblasts, where PAR 2 activation was associated with an elevated TNF-alpha release and PAR 1 activation prevented the release of proinflammatory cytokines. Interestingly, da Silva et al [47] showed that PAR 1 overexpression after periodontal treatment was inversely correlated to PAR 2 expression in gingival crevicular fluid cells.…”
Section: Discussionsupporting
confidence: 74%
“…In our previous studies, we reported that APC receptors EPCR, PAR-1 and PAR-2 are expressed by RA synovium (63,69) and APC inhibits the migration and activation of RA monocytes via EPCR (63). It is possible that ERK induction and downregulation of TNFα-stimulated p38, JNK and Akt in RSFs by APC will also be mediated by EPCR and PARs.…”
Section: Discussionmentioning
confidence: 99%
“…Human synovial tissues were fixed in 10% phosphate-buffered saline-buffered formalin. Immunohistochemical and immunofluorescent staining and toluidine blue staining were performed as described previously [26,27]. Isotype IgG for each antibody was used as a negative control.…”
Section: Methodsmentioning
confidence: 99%